Colistin Resistance in Pigs from Serbia: Bioinformatics Insight into mcr-1 Gene Sequencing - Petrovic, Danijela; Lalošević, Vesna; Kozoderović, Gordana; Vračar, Vuk; Lalošević, Dušan (Acta Scientiae Veterinariae, 2024)
Background: The increase of antimicrobial resistance is considered a major global threat for human and veterinary medicine. Misuse/overuse of antibiotics contributes to the rapid growth of resistance, also observed for colistin, a drug of choice in the therapy of human infections caused by multidrug resistant (MDR) bacteria. Due to wide usage of colistin as growth promoter in farm animals, the resistance of bacteria to this drug is of high concern in One Health perspective. In our previous study 10 mcr-1 positive PCR products from pigs’ faecal samples were identified and reported. The purpose of this study was to sequence these products and delve deeper into the colistin resistance via bioinformatics method. Materials, Methods & Results: Using a BLAST database, this study has identified mcr-1 gene variant(s) responsible for the spreading of resistance. A sequence-led approach identified these ten sequences and 100% alignment score was achieved by all tested (query) sequences. The query coverage for all sequences was between 98-100%, indicating that sequence in the database spans the most of the query sequence or the whole length of the query sequence, respectively. Eight sequences achieved 100%, while 1 reached 99% and 1 98% query coverage. The most of alignments originated in the Escherichia coli sequences (97%), followed by Klebsiella pneumoniae (2%) and Salmonella enterica (1%). All these pathogens are known as MDR bacteria, and in infections they caused, colistin is being used as salvage therapy. Based on the obtained BLAST results, we assumed that DNA isolated from pigs’ faecal samples originated from E. coli, although our samples were not cultured. The analysis revealed that these sequences were distributed predominantly in Asia, but also in South America and Europe, isolated from different farming animal species and humans, confirming global distribution across different species. Further comprehensive analysis yielded 37 functional genetic alleles of mcr-1 gene (mcr-1.1 – mcr-1.37) registered in NCBI database so far, and in order to identify possible mcr-1 gene alleles among tested sequences, additional BLAST alignment examinations were carried out. Five mcr-1 gene alleles were excluded as possible variants, but exact polymorphism in each of the sequences could not be confirmed, most likely due to the lack of full length of the tested sequences. These 10 sequences represent mcr-1 gene variant(s), registered in Serbia for the 1st time in pigs, and were submitted to the GeneBank and made publicly available, through the Accession numbers. Discussion: Plasmid-borne mcr-1 gene has become a significant cause for the dissemination of polymixin resistance in humans and animals worldwide. A closer inquiry in mcr-1 gene sequences helped to address mcr-1 gene contribution to the resistance spreading. It was revealed that identified mcr-1 gene sequences in pigs on Serbian farms have been already disseminated worldwide, on 3 continents, and in different species including farming animals (pigs, chicken, turkey) and their meat samples, companion animals (dogs) and humans. Our results indicated that mcr-1 gene sequencing contributes to the better understanding of colistin resistance molecular epidemiology. Necessity of colistin resistance monitoring in food producing animals as well as its prudent and responsible use on farms, since it is a last resort drug for combating infections in humans caused by multidrug resistant bacteria, is of crucial importance in One Health approach. Keywords: BLAST alignments, MDR, molecular epidemiology, colistin resistance, mcr-1 gene variants, Serbia.